DAMPAK KEBERADAAN ALAT TRANSPORTASI ONLINE TERHADAP BECAK KONVENSIONAL DI KOTA BANDA ACEH - Furqan, Furqan; Nurlaili, Nurlaili (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Developments in the field of technology have an impact on human life in various aspects, not least in the field of transportation. The development of technology inevitably affects people's mindsets. This condition also results in conventional rickshaws having decreased orders. The presence of online transportation causes competition such as injustice over the unequal income of each rickshaw puller and the increasing number of passengers in online transportation. This type of research is descriptive qualitative research. Data collection is done by conducting observations, interviews (interviews), documentation. The results showed that the characteristics inherent in conventional pedicab drivers are male, poorly educated, do not know the age limit, are Muslim and predominantly come from the Acehnese tribe. The presence of online application-based transportation in Banda Aceh has a positive impact in meeting the needs of transportation that is practical, safe, comfortable, and inexpensive, on the other hand online transportation has had an impact on conventional transportation namely conventional Pedicab drivers, Pedicab driver income has decreased orders so that driver deposit income conventional pedicabs are reduced every day. The presence of online transportation makes unsettled conventional rickshaw drivers, so online transportation drivers are less liked by conventional rickshaw drivers.Keywords: Impact, Conventional Pedicab, and Online.